Jet veto resummation for STXS H+1-jet bins at aNNLL′+NNLO - Pedro Cal; Matthew A. Lim; Darren J. Scott; Frank J. Tackmann; Wouter J. Waalewijn (Journal of High Energy Physics)
Abstract Measurements of Higgs boson processes by the ATLAS and CMS experiments at the LHC use Simplified Template Cross Sections (STXS) as a common framework for the combination of measurements in different decay channels and their further interpretation, e.g. to measure Higgs couplings. The different Higgs production processes are measured in predefined kinematic regions — the STXS bins — requiring precise theory predictions for each individual bin. In gluon-fusion Higgs production a main division is into 0-jet, 1-jet, and ≥ 2-jet bins, which are further subdivided in bins of the Higgs transverse momentum p T H $$ {p}_T^H $$ . Requiring a fixed number of jets induces logarithms ln p T cut / Q $$ {p}_T^{cut}/Q $$ in the cross section where p T cut $$ {p}_T^{cut} $$ is the jet-p T threshold and Q ∼ p T H $$ {p}_T^H $$ ∼ m H the hard-interaction scale. These jet-veto logarithms can be resummed to all orders in perturbation theory to achieve the highest possible perturbative precision. We provide state-of-the art predictions for the p T H $$ {p}_T^H $$ spectrum in exclusive H+1-jet production and the corresponding H+1-jet STXS bins in the kinematic regime p T cut $$ {p}_T^{cut} $$ ≪ p T H $$ {p}_T^H $$ ∼ m H . We carry out the resummation at NNLL ′ accuracy, using theory nuisance parameters to account for the few unknown ingredients at this order, and match to full NNLO. We revisit the jet-veto factorization for this process and find that it requires refactorizing the total soft function into a global and soft-collinear contribution in order to fully account for logarithms of the signal jet radius. The leading nonglobal logarithms are also included, though they are numerically small for the region of phenomenological interest.